Comparing population-general and sport-specific correlates of disordered eating amongst elite athletes: A cross-sectional study - Fatt, S. J.; George, E.; Hay, P.; Jeacocke, N.; Mitchison, D. (Sports Medicine - Open, 2024)
Background Despite the high prevalence of disordered eating and eating disorders amongst elite athletes, it remains unclear whether risk factors and psychological processes align with those in the general population or if there are unique sport-factors associated with heightened risk. This cross-sectional study investigated if sport-specific factors (including pressures and psychological processes) explained additional variance in elite athletes` disordered eating symptoms, controlling for established population-general risk factors. Current elite athletes (N = 178, 72.4% female, mean age = 23.9, standard deviation age = 7.0) completed online surveys assessing disordered eating, body dissatisfaction, perfectionistic traits, population-general and sport-specific pressures, as well as general (thin-ideal, muscular-ideal) and athlete-specific (drive for leanness for performance, athletic identity) psychological processes.